The Forensic Restrictiveness Questionnaire: Development, Validation, and Revision - Tomlin, Jack; Völlm, Birgit; Furtado, Vivek; Egan, Vincent; Bartlett, Peter (Frontiers in Psychiatry, 2019)
Forensic psychiatric care is often practiced in closed institutions. These highly regulated, secure and prescriptive environments arguably reduce patient autonomy, self-expression and personhood. Taken together these settings are restrictive as patients’ active participation in clinical, organizational, community and personal life-worlds are curtailed. The consequences of patients’ experiences of restrictiveness have not been explored empirically. This study aimed to develop a psychometrically-valid measure of experiences of restrictiveness. This paper presents the development, validation and revision of the Forensic Restrictiveness Questionnaire (FRQ). In total 235 patients recruited from low, medium and high secure hospitals across England completed the FRQ. The dimensionality of the 56-item FRQ was tested using Principle Axis Factor Analysis and parallel analysis. Internal consistency was explored with Cronbach’s α. Ward climate (EssenCES) and quality of life (FQL-SV) questionnaires were completed by participants as indicators of convergent validity. Exploratory Factor Analysis and Cronbach’s α guided the removal of items that did not scale adequately. The analysis indicated good psychometric properties. Exploratory Factor Analysis revealed a unidimensional structure, suggesting a single latent factor. Convergent validity was confirmed as the FRQ was significantly negatively correlated with quality of life (Spearman’s ρ=-0.72) and ward climate (Spearman’s ρ=-0.61). Internal consistency was strong (α=0.93). Forty-one items were removed from the pilot FRQ. The data indicate that a final 15-item FRQ is a valid and internally reliable measure. The FRQ offers a novel and helpful method for clinicians and researchers to measure and explore forensic patients’ experiences of restrictiveness within secure hospitals. within secure hospitals.